Gap junction remodelling in human heart failure is associated with increased interaction of connexin43 with ZO-1 - Bruce, Alexandra F. (Cardiovasc Res, 2008)
AIMS: Remodelling of gap junctions, involving reduction of total gap junction quantity and down-regulation of connexin43 (Cx43), contributes to the arrhythmic substrate in congestive heart failure. However, little is known of the underlying mechanisms. Recent studies from in vitro systems suggest that the connexin-interacting protein zonula occludens-1 (ZO-1) is a potential mediator of gap junction remodelling. We therefore examined the hypothesis that ZO-1 contributes to reduced expression of Cx43 gap junctions in congestive heart failure. METHODS AND RESULTS: Left ventricular myocardium from healthy control human hearts (n = 5) was compared with that of explanted hearts from transplant patients with end-stage congestive heart failure due to idiopathic dilated cardiomyopathy (DCM; n = 5) or ischaemic cardiomyopathy (ICM; n = 5). Immunoconfocal and immunoelectron microscopy showed that ZO-1 is specifically localized to the intercalated disc of cardiomyocytes in control and failing ventricles. ZO-1 protein levels were significantly increased in both DCM and ICM (P = 0.0025), showing a significant, negative correlation to Cx43 levels (P = 0.0029). There was, however, no significant alteration of ZO-1 mRNA (P = 0.537). Double immunolabelling demonstrated that a proportion of ZO-1 label is co-localized with Cx43, and that co-localization of Cx43 with ZO-1 is significantly increased in the failing ventricle (P = 0.003). Interaction between the two proteins was confirmed by co-immunoprecipitation. The proportion of Cx43 that co-immunoprecipitates with ZO-1 was significantly increased in the failing heart. CONCLUSION: Our findings suggest that ZO-1, by interacting with Cx43, plays a role in the down-regulation and decreased size of Cx43 gap junctions in congestive heart failure.